THE INFLUENCE OF PROFESSIONAL TEACHERS AND SCHOOL ACADEMIC CULTURE ON ELEMENTARY SCHOOL TEACHERS' PERFORMANCE IN TUMINTING DISTRICT, MANADO CITY - Selfia Montori (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Teacher performance is factor key in increase quality education basic . Efforts to improve teacher performance is not can separated from teacher professionalism , which is reflected in teacher certification and supported by culture academic conducive school . Research​ This aim For analyze the influence of professional and cultural teachers academic school , good in a way partial and simultaneously , against school teacher performance base in the District Tuminting , Manado City. Research This use approach quantitative with type study causal comparative . The method used is survey . Population study consists of from all school teachers base in the District Tuminting , with amount sample as many as 50 respondents . Data collection techniques use questionnaire based​​​ Likert scale compiled in a way systematic in accordance indicator variables research , as well as has through validity and reliability tests . Data analysis was carried out use multiple linear regression , which is preceded by with prerequisite tests analysis includes normality , linearity , and multicollinearity tests . The results of the analysis show that teacher certification has influence positive and significant to teacher performance , with t value of 2.863, level significance of 0.006 (p < 0.05), and the coefficient regression of 0.324. Culture academic schools also have an influence positive and significant to teacher performance , with t value of 6.188, level significance of 0.000 (p < 0.05), and the coefficient regression of 0.856. In general simultaneous , teacher certification and culture academic school influential significant to teacher performance , which is indicated by an F value of 40.160 with level significance of 0.000 (p < 0.05). Based on standardized beta coefficient , culture academic school is the most dominant variable influence teacher performance .